DEER KED (LIPOPTENA CERVI) DERMATITIS IN HUMANS – AN INCREASING NUISANCE IN FINLAND - Härkönen, Sauli; Laine, Maria; Vornanen, Martine; Reunala, Timo (Lakehead University, 2009)
The deer ked (Lipoptena cervi) is a haematophagous ectoparasite of moose (Alces alces) and other cervids that commonly bites humans in Finland. Since the 1970s there has been an increasing number of Finns who suffer from long-lasting and recurrent dermatitis associated with deer ked bites. Forestry workers, hunters, berry and mushroom pickers, and other people who work in or visit forests during late summer and early autumn are especially vulnerable to incidental deer ked infestation and dermatitis. Interestingly, negative effects of deer keds on human activities have not been recently reported in countries other than Finland. Our work indicates that dermatitis caused by deer keds consists of a few to 20-50 red papules which occur mostly on the scalp, neck, and upper back. The papules usually appear 6-24 h after the bites and size varies from a few mm to 1-2 cm. They can persist several weeks and in some people up to 1 year. The rapid range expansion of the deer ked in 1970-1990s seems related to the concurrent increase in moose population density in Finland. It is possible that range expansion of the deer ked will be promoted by high densities of semi-domesticated reindeer (Rangifer tarandus tarandus) in northern Finland. As a result, we predict an increase in the distribution of deer keds and the number of people with deer ked dermatitis requiring medical treatment in Finland.